CUMYL-4CN-BINACA Is an Efficacious and Potent Pro-Convulsant Synthetic Cannabinoid Receptor Agonist - Kevin, Richard C.; Anderson, Lyndsey; McGregor, Iain S.; Boyd, Rochelle; Manning, Jamie J.; Glass, Michelle; Connor, Mark; Banister, Samuel D. (Frontiers in Pharmacology, 2019)
Synthetic cannabinoid receptor agonists (SCRAs) are the largest class of new psychoactive substances (NPS). New examples are detected constantly, and some are associated with a series of adverse effects, including seizures. CUMYL-4CN-BINACA (1-(4-cyanobutyl)-N-(2-phenylpropan-2-yl)indazole-3-carboxamide) is structurally related to potent, cumylamine-derived SCRAs such as 5F-CUMYL-PINACA, but is unusual due to a terminal aliphatic nitrile group not frequently encountered in SCRAs or pharmaceuticals. We report here that CUMYL-4CN-BINACA is a potent, CB1 receptor agonist (Ki = 2.6 nM; EC50 = 0.58 nM) that produces pro-convulsant effects in mice at a lower dose than reported for any SCRA to date (0.3 mg/kg, i.p.). Hypothermic and pro-convulsant effects in mice could be reduced or blocked, respectively, by pre-treatment with CB1 receptor antagonist SR141716, pointing to at least partial involvement of CB1 receptors in vivo. Pre-treatment with CB2 receptor antagonist AM-630 had no effect on pro-convulsant activity. The pro-convulsant properties and potency of CUMYL-4CN-BINACA may underpin the toxicity associated with this compound in humans.